Influence and contribution of the platform economy to the digital economy - Ali, Yusifov (Dunakavics, 2024)
This study reviews key initiatives and research centers focused on the platform economy. Notable efforts include the MIT Digital Economy Initiative, which conducts research and organizes the Annual MIT Platform Strategy Summit, and Platformation Labs, which monitors trends in platform economics. Major consulting firms like Accenture also analyze platform business models and readiness. The Harvard Business School and Toulouse School of Economics are prominent in studying digital platforms, while the Observatory on the Online Platform Economy advises the European Commission on regulatory policies. Despite these advancements, challenges persist, such as the lack of a unified definition of the platform economy and inconsistent metrics across rankings. Current rankings, like those from the Boston Consulting Group and Forbes, show variability in criteria and methodology, underscoring the need for standardized evaluation methods. The study highlights the growing interest in platform economics but notes limitations in existing research frameworks and rankings, suggesting areas for future investigation.